Local coordination and medium range order in molten trivalent metal chlorides: The role of screening by the chlorine component - Pastore, G; Tatlipinar, H; Tosi, MP (GORDON BREACH SCI PUBL LTD, 1996)
Earlier work has identified the metal ion size R(M) as a relevant parameter in determining the evolution of the liquid structure of trivalent metal chlorides across the series from LaCl3(R(M) approximate to 1.4 Angstrom) to AlCl3(R(M) approximate to 0.8 Angstrom). Here we highlight the structural role of the chlorines by contrasting the structure of fully equilibrated melts with that of disordered systems obtained by quenching the chlorine component. Main attention is given to how the suppression of screening of the polyvalent ions by the chlorines changes trends in the local liquid structure (first neighbour coordination and partial radial distribution functions) and in the intermediate range order (first sharp diffraction peak in the partial structure factors). The main microscopic consequences of structural quenching of the chlorine component are a reduction in short range order and an enhancement of intermediate range order in the metal ion component, as well as the suppression of a tendency to molecular-type states at the lower end of the rang R(M).
Keywords: coordination number; partial structure factors; screening by chlorine; FLUID DISTRIBUTIONS; ARBITRARY MATRICES; EQUATIONS; EQUILIBRIUM; Chemistry; Physics